2022
DOI: 10.5435/jaaos-d-21-00657
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Extramedullary and Intramedullary Implants for Stable Intertrochanteric Fractures: Have We Swung the Pendulum Too Far the Other Way?

Abstract: Introduction: Although intramedullary implants are commonly used to treat stable intertrochanteric (IT) fractures, there is a lack of evidence to demonstrate their superiority over extramedullary implants in treating these fractures. The purpose of this study was to compare short-term outcomes (,30 days) between intramedullary and extramedullary implants in patients with closed nondisplaced stable IT fractures. Methods: Patients with closed nondisplaced stable IT fractures were identified from the American Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The studies that compare different types of extramedullary and intramedullary implants report facilitators of weight bearing favouring PFNA-II (compared with dynamic hip locking plates (DHLP)) [95], PFNA (compared with DHS) [52,65,72,94,96], PFN (compared with DHS) [68,76,77], short PFN (compared with DHS) [78], Mini-invasive static nail (compared with conventional DHS) [56], and gamma nail (compared with DHS) [71]. No difference between extramedullary and intramedullary implants was reported in two studies [54,85].…”
Section: Process (Surgical) (Table 3)mentioning
confidence: 99%
See 1 more Smart Citation
“…The studies that compare different types of extramedullary and intramedullary implants report facilitators of weight bearing favouring PFNA-II (compared with dynamic hip locking plates (DHLP)) [95], PFNA (compared with DHS) [52,65,72,94,96], PFN (compared with DHS) [68,76,77], short PFN (compared with DHS) [78], Mini-invasive static nail (compared with conventional DHS) [56], and gamma nail (compared with DHS) [71]. No difference between extramedullary and intramedullary implants was reported in two studies [54,85].…”
Section: Process (Surgical) (Table 3)mentioning
confidence: 99%
“…Okkaoğlu 2020 [79] − Tao 2013 [97] ✓ (B) Shu 2020 [84] ✓ (A) Peyser 2007 [80] ✓ (B) Torres 2014 [92] ✓ (B) Lunsjo 1999 [73] ✓ (D) Xie, 2017 [95] ✓ (B) Leung 1992 [71] ✓ (B) Duymus 2019 [58] ✓ (B) Kamboj 2019 [68] ✓ (B) Mayi 2016 [76] ✓ (B) Meesala 2018 [77] ✓ (B) Huang 2017 [65] ✓ (B) Chen 2018 [52] ✓ (B) Li 2018 [72] ✓ (B) Wang 2019 [94] ✓ (B) Xu 2018 [96] ✓ (B) Nargesh 2013 [78] ✓ (B) Singh 2021 [85] − Darbandi 2022 [54] − Dujardin 2001 [56] ✓ (B) Sandhu 2019 [82] ✓ (B) Jianbo 2019 [66] ✓ (A) Kaneko 2004 [69] ✓ (A) Karaali and Ciloglu 2021 [70] ✓ (B)…”
Section: Strengths and Limitations Of The Reviewmentioning
confidence: 99%
“…In principle, IM Nail is a stronger construct than the DHS fixation. 4 Therefore, many authors have suggested that DHS fixation can be used for most stable intertrochanteric fractures 5 but more unstable patterns should be treated by IM Nail. 6 Interestingly, several studies demonstrate that even the treatment of unstable fracture patterns using DHS has equal success rates of proper healing and therefore IM Nail fixation is not superior in stable or unstable fracture patterns.…”
Section: Introductionmentioning
confidence: 99%